Wnt Signaling Inhibits Osteoclast Differentiation by Activating Canonical and Noncanonical cAMP/PKA Pathways. (19th August 2015) - Weivoda, Megan M; Ruan, Ming; Hachfeld, Christine M; Pederson, Larry; Howe, Alan; Davey, Rachel A; Zajac, Jeffrey D; Kobayashi, Yasuhiro; Williams, Bart O; Westendorf, Jennifer J; Khosla, Sundeep; Oursler, Merry Jo
ABSTRACT: Although there has been extensive characterization of the Wnt signaling pathway in the osteoblast lineage, the effects of Wnt proteins on the osteoclast lineage are less well studied. We found that osteoclast lineage cells express canonical Wnt receptors. Wnt3a reduced osteoclast formation when applied to early bone‐marrow macrophage (BMM) osteoclast differentiation cultures, whereas late addition did not suppress osteoclast formation. Early Wnt3a treatment inactivated the crucial transcription factor NFATc1 in osteoclast progenitors. Wnt3a led to the accumulation of nuclear β‐catenin, confirming activation of canonical Wnt signaling. Reducing low‐density lipoprotein receptor‐related proteins (Lrp) 5 and Lrp6 protein expression prevented Wnt3a‐induced inactivation of NFATc1; however, deletion of β‐catenin did not block Wnt3a inactivation of NFATc1, suggesting that this effect was mediated by a noncanonical pathway. Wnt3a rapidly activated the cyclic adenosine monophosphate (cAMP)/protein kinase A (PKA) pathway and pharmacological stimulation of cAMP/PKA signaling suppressed osteoclast differentiation; Wnt3a‐induced NFATc1 phosphorylation was blocked by inhibiting interactions between PKA and A‐kinase anchoring proteins (AKAPs). These data indicate that Wnt3a directly suppresses osteoclast differentiation through both canonical (β‐catenin) and noncanonical (cAMP/PKA) pathways in osteoclast precursors. In vivo reduction of Lrp5 and Lrp6 expressions in the early osteoclast lineage via Rank promoter Cre recombination reduced trabecular bone mass, whereas disruption of Lrp5/6 expression in late osteoclast precursors via cathepsin K (Ctsk) promoter Cre recombination did not alter the skeletal phenotype. Surprisingly, reduction of Lrp5/6 in the early osteoclast lineage decreased osteoclast numbers, as well as osteoblast numbers. Published studies have previously noted that β‐catenin signaling is required for osteoclast progenitor proliferation. Our in vivo data suggest that Rank promoter Cre‐mediated deletion of Lrp5/6 may similarly impair osteoclast progenitor proliferation. © 2015 American Society for Bone and Mineral Research.